Pengaruh Sosial Media Dan Penggunaan Teknologi Informasi Terhadap Pendapatan UMKM Bandarjo Kecamatan Ungaran Semarang Jawa Tengah - Fitri, Intan Anissa; Siswanto, Edy (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of social media and information technology usage on the revenue of Micro, Small, and Medium Enterprises (MSMEs) in Bandarjo. The research method used was quantitative, with a survey approach through the distribution of questionnaires to 50 respondents from MSME traders in Bandarjo. Data were analyzed using multiple linear regression with the aid of SPSS software.The results showed that social media and information technology usage each had a positive and significant effect on MSME revenue, both partially and simultaneously. The regression coefficient for social media was 0.318 and for information technology usage was 0.343, with a significance level of 0.021 (<0.05). An F-test indicated that both variables jointly had a significant effect on MSME revenue (F = 17.177; Sig. = 0.01). The coefficient of determination (Adjusted R²) of 0.388 indicates that 38.8% of the variability in MSME revenue can be explained by social media and information technology usage. This study concludes that increased use of social media and information technology can positively contribute to increasing the revenue of MSMEs in Bandarjo. Therefore, MSMEs are advised to further optimize digital platforms and financial applications to support their business activities.